1995
DOI: 10.1006/ceps.1995.1022
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Influences of Maps and Diagrams on Learning

Abstract: Abstract:In this study, we examined the influence of graphic patterns and their interpretive context on learning accompanying prose. Subjects examined a graphic figure identified as either a map or a diagram and were instructed either to label its vertices with 12 keywords provided or to simply list them below the figure. Groups practiced performing their specific task from memory and given corrective feedback whereupon the entire procedure was repeated. Subjects then heard a narrated story with a different ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…They also rated diagrams as more effective than photographs for illustrations and were valued for assisting visualisation and understanding processes. Similarly, McCrudden et al (2007) found that 'causal diagrams improve comprehension by explicitly representing the implicit causal structure of the text in a visual format' while Kealy and Webb (1995) investigated how maps more than diagrams associated with text add value to the learning of concepts.…”
Section: Learning From Diagramsmentioning
confidence: 99%
“…They also rated diagrams as more effective than photographs for illustrations and were valued for assisting visualisation and understanding processes. Similarly, McCrudden et al (2007) found that 'causal diagrams improve comprehension by explicitly representing the implicit causal structure of the text in a visual format' while Kealy and Webb (1995) investigated how maps more than diagrams associated with text add value to the learning of concepts.…”
Section: Learning From Diagramsmentioning
confidence: 99%
“…A relatively large number of studies have focused on computer-aided, or computer-mediated, learning of graphics (e.g., Linn, Layman, & Nachmias, 1987;Lindwall, 1998;Lindwall & Ivarsson, 2004;Nemirovsky & Noble, 1997;Nemirovsky, Tierney, & Wright, 1998), whereas others deal with if-or to what extent-different types of graphic displays may enhance learning and recollection of subject matter (e.g., Kealy & Webb, 1995;Verdi, Kulhavy, Stock, Rittschof, & Johnson, 1996;Winn, 1991).…”
Section: Some Previous Researchmentioning
confidence: 99%
“…What about applications that coordinate interaction across multiple information views, the map being only one of them [108,109,221]? Does simply calling an application an "interactive map" change the way it is understood and used, as with the positive influence of using the term "map" instead of "diagram" [138,157]? Does the existential question of "what is an interactive map?"…”
Section: Seeing-thatmentioning
confidence: 99%